The moderating effect of probability of detection on the determinants influencing excise duty non-compliance in Malaysia - Sinnasamy, Perabavathi (Akademia Baru, 2017)
Tax non-compliance in indirect taxes involving importers as taxpayers in smuggling and illegal trade activities for cigarettes, liquor and imported vehicles exists as a complex phenomenon in Malaysia.The purpose of this study is to examine the direct relationship and probability of detection as moderator with tax audit, tax knowledge and peer influence as independent variables to determine excise duty non-compliance issue.The questionnaires were distributed using disproportionate stratified simple random sampling technique.A total of 500 useable questionnaires collected for analysis.The partial least square analysis applied to analyze the data.Analysis of data involved throughout Malaysia indicates the tax audit, peer influence and tax knowledge have a significant positive relationship.In addition, tax audit have significant negative relationship and tax knowledge have significant positive relationship with moderating effect.The findings from this study provided an indication for the tax administration in maximizing tax collections and encourage taxpayer’s compliance.